How Social Housing can Benerit from the Competitive Market - Emília Malcata Rebelo (2002)
This paper presents an analysis of statistical data, and develops a model of dwelling hedonic price level determination for the Oporto city (Portugal). This model is aimed to be a support to Municipal Planning decision processes, considering the complex inter-related system among the public powers and the free market functioning, involving different agents and their strategies, the administrative framework, the urban planning process and the municipal engineering. A cartographic interface was developed using geographic information systems, aimed to simulate alternative courses of municipal action, and to evaluate the expected results over housing price levels.A strategic proposal is made in order to transfer the responsibilities of the construction and management of the social housing sector to the private agents hands, suggesting that instead of the current system of dwelling support, a grant be allocated to the most needy families, so that they can choose their dwellings in the free market, thus contributing to their better social integration.